Scripturalizing Educational Elitism Social Formation, Mythmaking, and Symbolic Labor in Origen - McGinnis, Kevin (Claremont Studies in New Testament and Christian Origins, 2018)
An examination of the early writer, Origen, in light of contemporary theories on race, social status and personal location